2013
DOI: 10.5402/2013/569485
|View full text |Cite
|
Sign up to set email alerts
|

Paragonimiasis and Renewed Crab-Eating Behavior in Six Communities from Two Ethnocultural Clusters in Southeastern Nigeria

Abstract: is work was aimed at assessing the prevalence of paragonimiasis and crab-eating behavior in Southeastern Nigeria. Sputum examinations and questionnaire administration were carried out. Prevalence was 13.2% and was signi�cantly higher among females (14.6%) than males (11.2%) ( ). Overall, 77.2% of respondents across the communities eat crabs, and this was comparable between males (76.4%) and females (77.6%) ( ). e prevalence was comparable between the two ethnocultural groups and between communities within ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…This too agrees with the reports made by (Singh et al, 1986;Udonsi 1987;Uttah et al, 2013) but disagrees with the results of (Ibenga et al, 1997;Asor et al, 2003;Uttah, 2013) who reported that more females were infected than males. Many other researchers have reported no sex-related difference in prevalence (Uchiyama et al, 1999;Ashitani et al, 2000).…”
Section: Resultscontrasting
confidence: 55%
“…This too agrees with the reports made by (Singh et al, 1986;Udonsi 1987;Uttah et al, 2013) but disagrees with the results of (Ibenga et al, 1997;Asor et al, 2003;Uttah, 2013) who reported that more females were infected than males. Many other researchers have reported no sex-related difference in prevalence (Uchiyama et al, 1999;Ashitani et al, 2000).…”
Section: Resultscontrasting
confidence: 55%
“…reported that 79.3% (46/58) admitted a history of raw water or food ingestion. Changing dietary patterns are having a profound effect on the epidemiology of paragonimiasis 17 , 18 . Hence, it is necessary to appeal to change risky eating habits and strengthen the awareness of not taking raw water or food.…”
Section: Discussionmentioning
confidence: 99%
“…A survey in a different part of NE India did not detect a gender bias [ 7 ]. In one Nigerian study, women had a relatively high prevalence because they were more likely to eat crabs [ 8 ], perhaps while handling and preparing food, but prevalence was also high among fi shermen working in local rivers [ 142 ]. Cases of paragonimiasis due to P. kellicotti in the USA are nowadays mostly seen in male campers and canoeists who eat raw crayfi sh to show off [ 146 ].…”
Section: Cultural and Dietary Habits Aiding Transmissionmentioning
confidence: 99%
“…Of these, 20.9 % of children and 4.1 % of adults had eggs in their sputum. In SE Nigeria, 13.2 % of a population surveyed was eggpositive for paragonimiasis [ 8 ]. But it is important not to extrapolate too far from these focal data.…”
mentioning
confidence: 99%
See 1 more Smart Citation